Anxiety, health anxiety and somatosensory amplification levels in individuals with carpal tunnel syndrome with normal electromyography - Ali Gür; Savaş Gürsoy; Abdurrahman Altındağ; Bahadır Demir; Özlem Altındağ; Hacer Karaoglan; Mazlum Serdar Akaltun (Cukurova Medical Journal, 2021)
Purpose: The aim of this study was to investigate the levels of anxiety, health anxiety and somatosensory amplification in patients who presented with the clinical manifestation of Carpal Tunnel Syndrome (CTS) without electromyography findings. Materials and Methods: Patients who applied to the Physical Therapy and Rehabilitation outpatient clinic, respectively, and were diagnosed with CTS with clinical findings were included in the study. The patients who were determined to have no evidence of conduction loss in EMG were evaluated by using Short Health Anxiety Inventory (HAI-18), SomatoSensory Amplification Scale (SSAS), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Visual Analog Scale (VAS) and Boston Carpal Tunnel Questionnaire (BCTQ). Results: A total of 111 participants were included in the study, of whom 56 were patients and 55 were healthy control subjects. There was no significant difference between the patient and control groups in terms of age, gender, and body mass index (BMI). A statistically significant relationship was observed between these scales and the VAS, BCTQ symptom-severity and BCTQ function status in the positive direction. Conclusion: In our study, it was shown that the patient group showed higher anxiety, health anxiety and somatosensory amplification characteristics, and these features were associated with the severity of the CTS clinical scales. Studies with large-scale samples are needed to be carried out to confirm the results of this study.